Mental health context : mental health policy and service guidance package. (World Health Organization, 2003)
This introductory module describes the current global context of mental health. Beginning with an outline of the current burden of mental disorders, the module sets the stage by describing the historical background to the current situation and summarising recent developments in the understanding, treatment and care of people with mental disorders. An analysis is provided of trends in global health reform and their implications for mental health. To illustrate how these global trends can be addressed by governments, and to introduce the reader to the guidance package, a summary is then provided.